1993
DOI: 10.1111/j.1365-2249.1993.tb05994.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of α1-acid glycoprotein (AGP) gene induction following honey bee venom administration to adjuvant arthritic (AA) rats; possible role of AGP on AA development

Abstract: SUMMARYHoney bee venom (HBV) administration to adjuvatii arthritic (AA) rats resulted in a significanl suppression of arthritis and in suppression ofthe hepiitie acute phase ai-acid glycoprotein (AGP) gene induction at lhe early stages of disease development. AGPadniinislrationin A A rals resulted in acceleration of arthritis development and in increase of severity and duration of the disease, lL-1, IL-6. tumournecrosisfiictor(TNF)andglucocorticoidsalonearenol responsible for Ihc HBV-nicdiaied AGP gene down-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
16

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
0
8
0
16
Order By: Relevance
“…However, the same study (Kwon et al, 2001d) demonstrated that bee venom injected at the midline of the back is able to significantly reduce the same indicators of adjuvant-induced arthritis that develop after 12 days in the hind paw contralateral to adjuvant injection. Studies by other groups have also successfully inhibited signs of adjuvant-induced systemic polyarthritis with repeated bee venom injections at non-acupuncture points in the paws and on the back of rats (Chang and Bliven, 1979; Yiangou et al, 1993) indicating that injection at the acupuncture point is not critical to observe significant effects. Nonetheless, the same group has demonstrated that repeated bee venom injection (at acupuncture points) is anti-inflammatory in other rodent pain models including the prolonged type-II collagen-induced polyarthritis model (Lee et al, 2004).…”
Section: Anti-nociceptive and Anti-inflammatory Effects Of Bvtmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same study (Kwon et al, 2001d) demonstrated that bee venom injected at the midline of the back is able to significantly reduce the same indicators of adjuvant-induced arthritis that develop after 12 days in the hind paw contralateral to adjuvant injection. Studies by other groups have also successfully inhibited signs of adjuvant-induced systemic polyarthritis with repeated bee venom injections at non-acupuncture points in the paws and on the back of rats (Chang and Bliven, 1979; Yiangou et al, 1993) indicating that injection at the acupuncture point is not critical to observe significant effects. Nonetheless, the same group has demonstrated that repeated bee venom injection (at acupuncture points) is anti-inflammatory in other rodent pain models including the prolonged type-II collagen-induced polyarthritis model (Lee et al, 2004).…”
Section: Anti-nociceptive and Anti-inflammatory Effects Of Bvtmentioning
confidence: 99%
“…Reports from several research groups have demonstrated that bee venom injection can indeed reduce the inflammation evoked in a second inflammatory pain model including adjuvant-induced and type-II collagen-induced arthritis models and intraplantar injection of carrageenan (Chang and Bliven, 1979; Yiangou et al, 1993; Kwon et al, 2001d, 2002; Lee et al, 2004; Park et al, 2004). Although reproducible, this is paradoxical as bee venom injection itself produces signs of inflammation including marked edema, redness and nociception and hypersensitivity in rats and mice (Lariviere and Melzack, 1996; Chen et al, 1999b; Chen and Chen, 2000; Lariviere et al, 2005) and reports of pain and flare responses in human subjects receiving injections of bee venom components (Koyama et al, 2000, 2002), despite many claims from BVT proponents to the contrary.…”
Section: Anti-nociceptive and Anti-inflammatory Effects Of Bvtmentioning
confidence: 99%
“…Adjuvant arthritis (AA) was induced in rats as described previously (Yiangou et al, 1993b). Crystalline HBV (kindly provided by Mr. C. Mraz, Champlain Valley Apiaries, Middlebury, NY) was dissolved in saline and injected (0.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that in rats, AGP accelerates the onset of adjuvant arthritis (AA) and increases the severity and duration of the disease and that honeybee venom (HBV) completely suppressed AA development in rats while reducing liver AGP mRNA levels at the early stages of disease development (Hadjipetrou-Kourounakis and Yiangou 1984, 1988; Yiangou et al, 1993b). Our observations provide us with the biological system to study the mechanisms of the local action of AGP on AA development in rat joints and of the protective action of HBV.…”
Section: Introductionmentioning
confidence: 99%
“…After 54 h incubation at 378C and 5% CO 2 air, the cells were pulsed with 0.4 mCi of 3 H-TdR. Total 3 H-TdR incorporation was measured 18 hours later as we previously described (Yiangou et al 1993).…”
Section: Conditioning Medium (Cm)mentioning
confidence: 99%